Peran Pembelajaran Sirah Nabawiyah dalam Pembentukan Karakter Religius Peserta Didik - Ghossan Althof; Adi Haironi; Aminudin Jeri Satria (Jurnal Budi Pekerti Agama Islam, 2025)
This study examines the role of Sirah Nabawiyah learning in shaping students' religious character. Religious character is a fundamental aspect of Islamic teachings that reflects a person's closeness to Allah through attitudes, speech, and daily actions. Sirah Nabawiyah learning not only provides historical insights into the life of Prophet Muhammad but also serves as a holistic character education tool, encompassing relationships with Allah and with fellow human beings. This study employs a qualitative approach using literature study techniques. Data were collected through observation, interviews, and documentation, and analyzed using source triangulation techniques to ensure validity. The results indicate that values such as monotheism (tauhid), honesty, patience, compassion, and obedience to Allah can be instilled through a deep understanding of the life journey of Prophet Muhammad. Additionally, Sirah Nabawiyah learning helps strengthen students' Islamic identity, enabling them to practice Islamic teachings with confidence amid globalization. Thus, Sirah Nabawiyah learning significantly contributes to shaping a generation with noble character, high morality, and the ability to practice Islamic teachings with full awareness and responsibility. Therefore, integrating Sirah Nabawiyah into the Islamic education system is a strategic step in building a strong religious character in students.